Cuproptosis-related gene FDX1 expression correlates with the prognosis and tumor immune microenvironment in clear cell renal cell carcinoma - Wang, Tao; Liu, Yufeng; Li, Qing; Luo, Yang; Liu, Dawei; Li, Bin (Frontiers in Immunology, 2022)
Background Cuproptosis, a newly discovered form of cell death, is regulated by protein lipoylation and is related to mitochondrial metabolism. However, further research is needed to determine how the cuproptosis-related gene ferredoxin 1 (FDX1) affects the tumor immune response and its prognostic significance in clear cell renal cell carcinoma (ccRCC). Methods The Cancer Genome Atlas was used to screen for FDX1 gene expression in ccRCC and healthy tissue samples. The results were validated using the Gene Expression Omnibus and the Human Protein Atlas. Multivariable analysis and Kaplan-Meier survival curves were used to examine the relationship between FDX1 gene expression, clinicopathological parameters, and overall survival (OS). The protein network containing FDX1 gene interaction was constructed using the online Search Tool for the Retrieval of Interacting Genes/Proteins. The relationship between FDX1 gene expression and immune cell infiltration in ccRCC was examined using Gene Ontology, gene set enrichment analysis (GSEA), and a single-sample GSEA. Using the Gene Expression Profiling Interactive Analysis and Tumor Immune Estimation Resource databases, we investigated the relationship between FDX1 gene expression, the degree of immune cell infiltration, and the corresponding gene marker sets. Results ccRCC samples had significantly (p < 0.05) lower FDX1 gene expression levels than normal tissue samples. Lower FDX1 gene expression levels were strongly associated with higher cancer grades and more advanced tumor–node–metastasis stages. The findings of multivariate and univariate analyses illustrated that the OS in ccRCC patients with low FDX1 expression is shorter than in patients with high FDX1 expression (p < 0.05). Ferredoxin reductase and CYP11A1 are key proteins interacting with the FDX1 gene, and ccRCC with an FDX1 enzyme defect was associated with a low number of invading immune cells and their corresponding marker. Conclusion In ccRCC, decreased FDX1 expression was linked to disease progression, an unfavorable prognosis, and dysregulated immune cell infiltration.